Drug-Related Deaths in China: An Analysis of a Spontaneous Reporting System - Li, Haona; Deng, Jianxiong; Yu, Peiming; Ren, Xuequn (Frontiers in Pharmacology, 2022)
Background: Adverse drug reactions with an outcome of death represent the most serious consequences and are inherently important for pharmacovigilance. The nature and characteristics of drug-related deaths are to a large extent unknown in the Chinese population. This study aims to characterize drug-related deaths by analysis of Individual Case Safety Reports (ICSRs) with an outcome of death in China. Methods: Characteristics of death ICSRs were analyzed by descriptive statistics of a large multi-provincial pharmacovigilance database in China. Results: There were 1731 ICSRs with an outcome of death, representing 0.95% of all serious cases, and 0.05% of all reported ICSRs. Most death ICSRs (78.57%) were reported by medical institutions. Only 16.00% of death ICSRs were reported by manufacturers or distributors. The reporting rate of death ICSRs in the age group of 0-4 was significantly higher than patients aged 5-64. Patients aged over 64 had the highest reporting rate of death ICSRs. Males generally had a higher reporting rate of death ICSRs than females. However, the reporting rate of females exceeded that of males in the age group of 20-34. Among 3861 drugs implicated, Ceftriaxone sodium with 146 (3.78%) records of death ranked first. Dexamethasone with 131 (3.39%) records of death ranked second. Qingkailing, an injectable traditional Chinese medicine, with 75 (1.94%) records of death ranked the fifth most frequently implicated medicine. Conclusions: Young children and elderly patients have higher risk of drug-related deaths than patients aged 5-64. Females generally have lower risk of drug-related deaths than males. However, female patients of reproductive age (aged 20-34) have higher risk of drug-related deaths than males, hinting that physiological changes and drug uses for child bearing, giving birth or birth control may significantly increase the risk of death for females aged 20-34. This paper suggests more research on the safety use of drugs for young children, elderly patients, and females of reproductive ages. Pharmacovigilance databases can be valuable resources for comprehensive understanding of drug-related problems.